Aesthetic Treatment In Patient With Fractures Of Maxillary Central Incisor Teeth - Sinta Puspita (Denta Journal Kedokteran Gigi, 2017)
Background : A common objective of anterior restorative dentistry is to establish anterior guidance between the maxillary and mandibular anterior teeth to disclude the posterior teeth during protrusive mandibular movement. Fracture anterior teeth leads to psychological trauma, along with functional and esthetic debilitations. Healthy anterior teeth play an important role of protecting the posterior teeth during excursive mandibular movement. The contour and shape of the labial surface are important for esthetic purpose; the palatal surface morphology is critical for harmonious function. Premature contact in palatal surface restoration is considered as contributing factor to temporomandibular disorder (TMD) symptoms. Purpose : Improve aesthetics and function of the patient's anterior teeth. Case : Male, 17 years old with poor aesthetic because of fracture anterior teeth 4 years ago. Case Management : Root canal treatment, treatment of root resorption, fiber post, custom post, indirect veener, zirconia crown and enameloplasty. Result : Better aesthetic and get the optimum function of his teeth.